Quick and smart corn peeler / Muhammad Amirul Syahmee Mohd Baseri - Mohd Baseri, Muhammad Amirul Syahmee (2022)
Corn peelers from the past were usually used with knives or any other cutting tools to extract the kernels from the cob before the next processing took place. However, most of those conventional methods problems encountered in corn peeling are adding more human energy needed, making it take a long time to finish each corn peeler, and likewise, which is probably going to provide a risk of wounds due to a sharp corn peeler like a knife blade. So, the tool that will be made is to obtain a reduction in human energy, the production of goods in a shorter time, and it is more secure to use. The goal of the corn peeler that was chosen to be designed and fabricated is to make it easier for users to peel corn more easily than the corn peeler that has been released before in order to add more benefits, such as obtaining a reduction in human energy, producing goods in a shorter time, and it is more secure to use. The corn peeler method used is to twist the corn at blade corn with one one-way route only to smooth out all the whole grains of the corn peeler.Thus, a new method of corn peeling is necessary to obtain a more convenient and safe cutting technique in order to eliminate the existing drawback.Then, the finalised concept was interpreted as a three-dimensional (3-D) model comprising three main parts, namely body, handle, and container, which were designed using SolidWork. For this project demonstrates the need to design a small project for corn peeling.Before the prototype was produced, design parameters, size considerations, and material choices were researched. Testing was done to make sure the prototype was as effective as possible, especially in getting a good technique for corn peeling.Therefore, can solve the problem of corn peelers by being able to obtain a reduction in human energy, producing goods in a shorter time, and it is more secure to use.